2021
DOI: 10.1186/s13148-021-01040-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA methylation in Hirschsprung enteric precursor cells: unraveling the epigenetic landscape of enteric nervous system development

Abstract: Background Hirschsprung disease (HSCR, OMIM 142623) is a rare congenital disorder that results from a failure to fully colonize the gut by enteric precursor cells (EPCs) derived from the neural crest. Such incomplete gut colonization is due to alterations in EPCs proliferation, survival, migration and/or differentiation during enteric nervous system (ENS) development. This complex process is regulated by a network of signaling pathways that is orchestrated by genetic and epigenetic factors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A broader whole genome methylation analysis found that enteric precursor cells obtained from patients with HSCR exhibited an overall pattern of DNA hypomethylation compared with controls (Ref. 66). These findings are in agreement with data demonstrating reduced expression of the DNA methyltransferase DNMT3B in neural progenitor cells in the setting of HSCR (Ref.…”
Section: Dna Methylation In Intestinal Diseasementioning
confidence: 99%
“…A broader whole genome methylation analysis found that enteric precursor cells obtained from patients with HSCR exhibited an overall pattern of DNA hypomethylation compared with controls (Ref. 66). These findings are in agreement with data demonstrating reduced expression of the DNA methyltransferase DNMT3B in neural progenitor cells in the setting of HSCR (Ref.…”
Section: Dna Methylation In Intestinal Diseasementioning
confidence: 99%
“…Extensive research underscores the pivotal roles these methyltransferases assume in both intestinal and ENCCs development [ [95] , [96] , [97] ]. Villalba-Benito et al [ 98 ] observed a reduction in the overall level of DNA methylation in EPCs derived from HSCR patients. Furthermore, aberrant DNA methylation patterns were found in certain key genes associated with ENS development, such as RET, GFRA4, EDNRB, SOX10, PHOX2B, and NRG1 [ [99] , [100] , [101] , [102] ].…”
Section: Non-coding Rna Classes Associated With Hscrmentioning
confidence: 99%
“…Furthermore, aberrant DNA methylation patterns were found in certain key genes associated with ENS development, such as RET, GFRA4, EDNRB, SOX10, PHOX2B, and NRG1 [ [99] , [100] , [101] , [102] ]. Intriguingly, Villalba-Benito et al [ 98 ] discerned that specific ncRNAs related to HSCR, such as MEG3, AFAP1-AS, IPW, NR2F1-AS1, and miR-195, exhibited aberrant DNA methylation patterns in differential methylation region (DMR) analysis. Notably, the aberrant expression of MEG3, AFAP1-AS and miR-195 has been shown to inhibit the migration and proliferation of ENCCs [ 38 , 66 , 73 ].…”
Section: Non-coding Rna Classes Associated With Hscrmentioning
confidence: 99%
“…These small noncoding RNAs control gene expression post-transcriptionally, by base-pairing to partially complementary sequences in target messenger RNAs ( Bartel, 2004 ). Our knowledge of microRNAs and their role in ENS development is only beginning ( Kang et al, 2021 ), also mostly starting from uncovering their expression and possible roles in Hirschsprung disease ( Sergi et al, 2016 ; Villalba-Benito et al, 2021 ).…”
Section: Factors That Control Glial Differentiationmentioning
confidence: 99%